Injection Molding of Magnesium Aluminate Spinel Nanocomposites for High‐Throughput Manufacturing of Transparent Ceramics. Issue 31 (4th September 2022) - Mader, Markus; Prediger, Richard; Schell, Karl G.; Schmidt, Gabriela; Dorn, Alex; Jenne, Sophie; Kluck, Sebastian; Hambitzer, Leonhard; Luitz, Manuel; Schwarz, Claudia; Milich, Marcel; Greiner, Christian; et al.
Abstract: Transparent ceramics like magnesium aluminate spinel (MAS) are considered the next step in material evolution showing unmatched mechanical, chemical and physical resistance combined with high optical transparency. Unfortunately, transparent ceramics are notoriously difficult to shape, especially on the microscale. Therefore, a thermoplastic MAS nanocomposite is developed that can be shaped by polymer injection molding at high speed and precision. The nanocomposite is converted to dense MAS by debinding, pre‐sintering, and hot isostatic pressing yielding transparent ceramics with high optical transmission up to 84 % and high mechanical strength. A transparent macroscopic MAS components with wall thicknesses up to 4 mm as well as microstructured components with single micrometer resolution are shown. This work makes transparent MAS ceramics accessible to modern high‐throughput polymer processing techniques for fast and cost‐efficient manufacturing of macroscopic and microstructured components enabling a plethora of potential applications from optics and photonics, medicine to scratch and break‐resistant transparent windows for consumer electronics. Abstract : The development of thermoplastic magnesium aluminate spinel (MAS) nanocomposites allows the fabrication of 3D, transparent MAS with single micron resolution using high‐throughput polymer injection molding. The injection molded nanocomposites are subsequently converted to dense and transparent MAS using debinding, pre‐sintering, and hot isostatic pressing. The injection molded MAS shows high optical transparency, low surface roughness, and high mechanical stability.